Pengaruh Infrastruktur Listrik dan Infrastruktur Sosial terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Adrisa Auldri; Puti Andiny; Yani Rizal; Safuridar Safuridar (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study was conducted to analyze the effect of Electricity infrastructure and social infrastructure on economic growth in Aceh Province. The purpose of this study is to determine and explain the effect of how the influence of Electricity, Health and Education infrastructure on economic growth in Aceh Province. Data analysis in this study is using Multiple Linear Regression. This type of research data is quantitative research and secondary data. Data sources are obtained from the Central Bureau of Statistics (BPS). The results of this study indicate that Electricity infrastructure which has a probability value of 0.2855> 0.05 has no effect on economic growth. health infrastructure which has a probability value of 0.5845> 0.05 has no effect on economic growth. education infrastructure which has a probability value of 0.3478> 0.05 has no effect on economic growth. So it can be concluded that the variables of Electricity, Health and Education are not significant to economic growth in Aceh Province.